2022
DOI: 10.4041/kjod.2022.52.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of one-step automated orthodontic diagnosis model using a convolutional neural network and lateral cephalogram images with different qualities obtained from nationwide multi-hospitals

Abstract: Objective The purpose of this study was to investigate the accuracy of one-step automated orthodontic diagnosis of skeletodental discrepancies using a convolutional neural network (CNN) and lateral cephalogram images with different qualities from nationwide multi-hospitals. Methods Among 2,174 lateral cephalograms, 1,993 cephalograms from two hospitals were used for training and internal test sets and 181 cephalograms from eight other hospitals were used for an external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Yu et al 31 investigated the ability of a DenseNet AI model in identifying vertical skeletal and sagittal classes from lateral cephalograms. Similar results were seen as compared to Yim et al 30 where the sensitivity scores were 6-7% lower than the speci city scores across all reported skeletal and sagittal classes. However, the study authors reported an imbalanced dataset and opted to under-sample the data where 882 images were excluded from the study to ensure equal group weighting.…”
Section: Orthodonticssupporting
confidence: 86%
See 2 more Smart Citations
“…Yu et al 31 investigated the ability of a DenseNet AI model in identifying vertical skeletal and sagittal classes from lateral cephalograms. Similar results were seen as compared to Yim et al 30 where the sensitivity scores were 6-7% lower than the speci city scores across all reported skeletal and sagittal classes. However, the study authors reported an imbalanced dataset and opted to under-sample the data where 882 images were excluded from the study to ensure equal group weighting.…”
Section: Orthodonticssupporting
confidence: 86%
“…In this section, four studies were included, with two detecting supernumerary teeth (ST) 22,26 and the other two relating to skeletal classi cation 30,31 . Mine et al 22 investigated the effectiveness of an AI model in detecting single and double ST in the early mixed dentition stage using panoramic radiographs.…”
Section: Orthodonticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial intelligence-assisted automated detection of the landmarks and evaluation of the skeletal and dental discrepancies is getting popular. 23,[26][27][28] However, it is still necessary to develop the artificial intelligence-assisted virtual surgical planning to reduce clinician's laborious and time-consuming works, to simulate the amount and direction of the required surgical movement, and to provide a preview of surgical outcome. However, for accurate prediction of the soft tissue change, it is mandatory to check surgical accuracy between virtually surgical simulation and actual surgical movements of the maxilla and mandible in the 3D coordinates.…”
Section: Clinical Implications Of the Results From This Studymentioning
confidence: 99%
“…CNNs have been applied to cephalometric analysis to automatically detect cephalometric landmarks and analyze patients' facial skeletal, dental, and soft tissue patterns. 2,3 Since the first application of computer vision technologies to automatically identify the sella and menton in lateral cephalograms in 1984, 4 algorithms for automated cephalometric analysis have evolved. Owing to the increased capacity of computing power to analyze and extract features from a large amount of data in a short amount of time, various AI-based cephalometric analysis algorithms have been developed, with mean error values ranging from 1.1 to 4.09 mm.…”
Section: Backg Rou N Dmentioning
confidence: 99%